2017
DOI: 10.1086/689605
|View full text |Cite
|
Sign up to set email alerts
|

Differential Survival between Visual Environments Supports a Role of Divergent Sensory Drive in Cichlid Fish Speciation

Abstract: Online enhancements: appendix. Dryad data: http://dx.doi.org/10.5061/dryad.6nh3j.abstract: Identifying the selective forces that initiate ecological speciation is a major challenge in evolutionary biology. Sensory drive has been implicated in speciation in various taxa, largely based on phenotype-environment correlations and signatures of selection in sensory genes. Here, we present a reciprocal transplant experiment revealing species differences in performance in alternative visual environments, consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 64 publications
2
39
0
Order By: Relevance
“…We further show that hybridisation-derived variants are enriched in genes related to vision, pathogen defence and non-coding and ribosomal RNA function. The former two categories have previously been implicated to play a role in speciation and adaptive radiation in cichlids or other fishes (Carleton et al 2005;Malmstrøm et al 2016;Maan et al 2017;Meier et al 2017;Malinsky et al 2018) . In particular, Meier et al (2017) have shown that in the LVRS divergent parental haplotypes of a short-wavelength opsin gene differentiate clear shallow water algivores from deep turbid water detritivores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further show that hybridisation-derived variants are enriched in genes related to vision, pathogen defence and non-coding and ribosomal RNA function. The former two categories have previously been implicated to play a role in speciation and adaptive radiation in cichlids or other fishes (Carleton et al 2005;Malmstrøm et al 2016;Maan et al 2017;Meier et al 2017;Malinsky et al 2018) . In particular, Meier et al (2017) have shown that in the LVRS divergent parental haplotypes of a short-wavelength opsin gene differentiate clear shallow water algivores from deep turbid water detritivores.…”
Section: Discussionmentioning
confidence: 99%
“…5). Both genes related to vision and to pathogen defence have previously been suggested to play a role in speciation (Carleton et al 2005;Malmstrøm et al 2016;Egger et al 2017;Maan et al 2017;Meier et al 2017;Malinsky et al 2018) . Consistent with the results above, we find that even genes in these categories do not show long hybridisation-derived haplotypes, that is, most fixed differences between Ruaha Blue and Victoria in these regions are not variable in Malawi .…”
Section: Hybridisation-derived Variants Are Enriched In Vision-and Immentioning
confidence: 99%
“…Also in contrast to prior work (Dijkstra, Zee, & Groothuis, ; Haesler & Seehausen, ; Seehausen & van Alphen, ; van der Sluijs et al, ), we limited the opportunity for maternal imprinting (Verzijden & ten Cate, ; Verzijden, Korthof, & Cate, ) by removing fish from brooding females at 5 – 6 days post‐fertilization, possibly reducing preference strength. Finally, we are now aware of light‐induced survival differences in our laboratory population: when reared in “unnatural” light conditions, while all other parameters are kept the same, both species survive at a lower rate (~40% reduction at 12 months) than their “naturally” reared counterparts (Maan et al, ). Nonrandom survival could have generated a population of relatively flexible test females, exhibiting weak species specificity in behaviour including mate choice.…”
Section: Discussionmentioning
confidence: 99%
“…Our manipulated light conditions were created to mimic the natural light environments of the blue and red species at Python Islands, Lake Victoria (described in greater detail in: Maan, Seehausen, & Groothuis, ). Briefly, we used halogen light bulbs filtered with a green light filter (LEE # 243, Andover, UK) in both conditions.…”
Section: Methodsmentioning
confidence: 99%
“…'pundamilia-like') and one with red/yellow male coloration (P. nyererei and P. sp. both species survive best in their own natural light condition [13].…”
mentioning
confidence: 99%